1974
DOI: 10.2466/pms.1974.38.3.815
|View full text |Cite
|
Sign up to set email alerts
|

Visual Imagery and Hypnotic Susceptibility

Abstract: A dot-pattern test for accuracy of imagery and the Betts QMI scale for vividness of self-reported imagery were administered to 10 Ss high and 10 Ss low in hypnotic susceptibility. As in previous studies, susceptibility and Betts scale responses were related, but neither was related to dot-pattern performance. Results emphasize the complexity of the concept of imagery and the variety of possible bases for the relationship between self-reported imagery and hypnotic susceptibility, such as response-bias, suggesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1980
1980
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Ham, & M.L. ; Sutcliffe, Perry, & Sheehan, 1970;Wagman & Stewart, 1974).4 Gaupp (1975) found that hypnosis used with high susceptible Ss was not effective in enhancing imagery above the level found in a similarly constituted control group. The control Ss in this study, however, were not the usual waking controls; instead, these Ss received a progressive relaxation treatment which could be viewed as a hypnotic induction, Thus, the questions: Is hypnotic induction a critical factor, or is it simply that individuals who respond well to hypnosis are already good at imaging?…”
mentioning
confidence: 96%
“…Ham, & M.L. ; Sutcliffe, Perry, & Sheehan, 1970;Wagman & Stewart, 1974).4 Gaupp (1975) found that hypnosis used with high susceptible Ss was not effective in enhancing imagery above the level found in a similarly constituted control group. The control Ss in this study, however, were not the usual waking controls; instead, these Ss received a progressive relaxation treatment which could be viewed as a hypnotic induction, Thus, the questions: Is hypnotic induction a critical factor, or is it simply that individuals who respond well to hypnosis are already good at imaging?…”
mentioning
confidence: 96%
“…However, it consists of 150 items and is often considered prohibitively long. Wagman and Stewart (1974) found a five-factor structure with single or combined modalities, while Campos and Perez-Fabello (2005) found eight factors in a Spanish translation, six matching modalities from the English original. Richardson (1994, pp.…”
mentioning
confidence: 99%
“…Test-retest reliability for the Sheehan-Betts QMI has been found to be 0.75 for females and 0.72 for males after 2 weeks (Westcott and Rosenstock 1976). Factor analyses of the questionnaire items have revealed the presence of a large unitary factor corresponding to general vividness of imagery and modality specific factors (Sheehan 1967;Wagman and Stewart 1974;White et al 1974).…”
Section: Methodsmentioning
confidence: 94%